When the "Golden Years" turn blue: Using the healthy aging literature to elucidate anxious and depressive disorders in older adulthood. (March 2017) - Green, Jennifer S.; Magee, Joshua C.; Steiner, Amanda R.W.; Teachman, Bethany A.
Current treatments for disorders of emotion, such as pathological anxiety, are often less effective in older adults than in younger adults and have poorly understood mechanisms, pointing to the need for psychopathology models that better account for age-related changes in normative emotional functioning and the expression of disordered emotion. This article describes ways in which the healthy aging and emotion literature can enhance understanding and treatment of symptoms of anxiety and depression in later life. We offer recommendations on how to integrate the theories and findings of healthy aging literature with psychopathology research and clinical practice and highlight opportunities for future research.